Parking Strategies for Vertical Axis Wind Turbines. (14th November 2012) - Ottermo, F.; Eriksson, S.; Bernhoff, H.
Abstract : Strategies for parking a vertical axis wind turbine at storm load are considered. It is proposed that if a directly driven permanent magnet synchronous generator is used, an elegant choice is to short-circuit the generator at storm, since this makes the turbine efficiently damped. Nondamped braking is found to be especially problematic for the case of two blades where torsional oscillations may imply thrust force oscillations within a range of frequencies.